HIV treatment satisfaction: HIVTSQ-12 factor analysis and associated factors in Türkiye - Ilkay Akbulut; Zeynep Sedef Varol; Ilker Ödemiş; Emel Eroğul; Sabri Atalay; Ayşe Deniz Gökengin (BMC Infectious Diseases)
Abstract Background Despite global efforts, HIV/AIDS remains a significant public health challenge, with Türkiye witnessing a consistent rise in annual diagnoses. Patient satisfaction with antiretroviral therapy (ART) is crucial for treatment adherence and effectiveness. This study examines treatment satisfaction levels among people living with HIV (PLWH) in Türkiye and identifies associated factors. Materials and methods A cross-sectional prospective cohort study was conducted at Tepecik Training and Research Hospital, Izmir, Türkiye, involving 238-PLWH receiving ART. Data were collected through face-to-face interviews using the HIV Treatment Satisfaction Questionnaire (HIVTSQ-12) and demographic/clinical forms. Confirmatory Factor Analysis and descriptive statistics were employed for data analysis. Results Participants exhibited high overall treatment satisfaction, with significant associations between satisfaction levels and socio-demographic/clinical factors. Individuals with lower education levels, no substance use, minimal alcohol consumption, and suppressed viral loads reported higher satisfaction scores. Conclusion This study highlights the potential for personalizing HIV treatment strategies based on socio-demographic and clinical factors. Findings emphasize the need to promote healthy lifestyles, enhance health literacy, and implement anti-addiction programs to improve treatment adherence and satisfaction among PLWH. Based on the findings, there is a need to develop strategies aimed at improving treatment satisfaction and outcomes in HIV management.